Pengaruh Pemberian ASI Eksklusif di BPM Maimunah Palembang - Rahmalia Afriyani; Ika Savitri; Nur Sa'adah (Jurnal Kesehatan, 2018)
Breast milk is the best food for an infant. Toddlers are faster affected by the chronic diseases such as cancer, heart disease, hypertension, and diabetes when they grow up. The main causes are less quality of getting the exclusive breastfeeding. The percentage of exclusive breastfeeding in Maimunah’s midwifery lab work was only77,09% in 2016. The purpose of this study was to determine those factors that influenced exclusive breastfeeding in Maimunah’s midwifery lab work Palembang. This study was about a quantitative one with a cross-sectional approach and carried on 2nd-15th of August 2016. There were 94 qualified respondents and the data collection was done by using the questionnaire. The data were analyzed by frequency test, chi-square test, and logistic regression. The shown that 62.8% who gave the exclusive breastfeeding, 55,3% didn’t work,  47,9% were in an age of 20-30, 59,6% had high education, and 63,8% had children ≥2. Meanwhile, there was a significant relationship between exclusive breastfeeding with the occupation (p-value=0.000), age (p-value=0.025), education  (p-value=0,020), and parity (p-value=0.022). The result of multivariate analysis shown that influential factors of exclusive breastfeeding were occupational, age and parity. Furthermore, the most influential factor was an occupation with OR = 10.197.  It was suggested to improve the motivation of working mothers to have the exclusive breastfeeding by facilitating them with the corner of breastfeeding in their office.